Influence of Organic Solvent Species on Dehydration Behaviors of NaA-Type Zeolite Membrane - Yasuhisa Hasegawa; Wakako Matsuura; Chie Abe; Ayumi Ikeda (Membranes, 2021)
In this study, an NaA-type zeolite membrane was prepared, and the dehydration performances of the membrane were determined by the pervaporation for several organic solvents to understand the lower dehydration performances of zeolite membranes for NMP solutions than those for alcohols. For a 90 wt% ethanol solution at 348 K, the permeation flux and separation factor of the membrane were 3.82 kg m−2 h−1 and 73,800, respectively. The high dehydration performances were also obtained for alcohols and low boiling solvents (acetonitrile, acetone, methyl ethyl ketone (MEK) and tetrahydrofuran (THF)). However, the permeation flux and separation factors decreased significantly for high boiling solvents, such as N,N-dimethylacetamide (DMA), N,N-dimethyl formamide (DMF), dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidone (NMP). The influences of the water content and temperature on the dehydration performances for the NMP solutions were determined to understand the lower dehydration performances for those solvents. Those results suggest that the lower dehydration performances for the high boiling solvents were attributed to the lower vapor pressures of water and the higher permeances of those solvents. Furthermore, this study proposes that the permeation behaviors through zeolite membranes could be understood by the determination of the effect of temperature on the permeance of individual components.